2010
DOI: 10.1017/s1754470x10000139
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the training of clinical supervisors: a pilot study using the fidelity framework

Abstract: Theevaluation of supervisor training has featured weak measurement and lacked a coherent framework, limiting effectiveness. A literature review was first conducted to clarify the current status of supervisor workshop evaluations, related to the promising fidelity framework. This consists of five criteria: the workshop's design, the training (competence of the trainer), the delivery of the workshop, the learning of the participants (receipt), and the clinical practice outcomes (enactment). Second, we applied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…An assessment of participants’ understanding was included in 20 (60.6%) studies [25, 29, 31, 3337, 39, 45, 47, 48, 50, 57, 61, 65, 67, 73, 75, 78] and an assessment of participants’ performance of intervention-related skills in 14 (42.4%) studies [3336, 45, 47, 48, 51, 54, 56, 57, 65, 75, 78]. With regards to strategies to enhance receipt, 4 (12.1%) studies reported using a strategy to enhance participants’ understanding [41, 48, 56, 57], 7 (21.1%) to enhance performance of intervention-related skills [39, 41, 44, 47, 48, 56, 57].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An assessment of participants’ understanding was included in 20 (60.6%) studies [25, 29, 31, 3337, 39, 45, 47, 48, 50, 57, 61, 65, 67, 73, 75, 78] and an assessment of participants’ performance of intervention-related skills in 14 (42.4%) studies [3336, 45, 47, 48, 51, 54, 56, 57, 65, 75, 78]. With regards to strategies to enhance receipt, 4 (12.1%) studies reported using a strategy to enhance participants’ understanding [41, 48, 56, 57], 7 (21.1%) to enhance performance of intervention-related skills [39, 41, 44, 47, 48, 56, 57].…”
Section: Resultsmentioning
confidence: 99%
“…Given the focus of the forward citation search on the BCC framework, the two most common ways of assessing receipt in the 55 studies reviewed were measurements of understanding, included in 26 (47.3%) studies [25, 29–31, 3337, 39, 40, 45, 47–50, 57, 6062, 65, 67, 70, 73, 75, 78], and of performance of skills, included in 16 (29.1%) studies [3336, 45, 47, 48, 51, 54, 56, 57, 65, 70, 71, 75, 78]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through direct observation and the use of standardized checklists (Bellg et al 2004). A small-scale but explicit application of this fidelity framework has suggested that this kind of systematic evaluation of supervisor training is feasible, albeit with weak instrumentation in this 'case study' (Culloty et al 2010). …”
Section: Strategies To Improve Training In Supervisionmentioning
confidence: 96%
“…Applying the Fidelity Framework to the Evaluation o f Outcomes From Clinical Supervision, With Illustrative Methods and StudiesWeingardt, Cucciare, Bellotti, & Lai (2009): Designed a "blended learning" system, featuring e-leaming with a self-paced, online course in CBT plus a series of live, online virtual group supervision sessions, designed to promote adherence Culloty, Milne, & Sheikh (2010)…”
mentioning
confidence: 99%